Peranan Diplomat Indonesia dalam Memperjuangkan Palestina di PBB (Masa Presidency of the UNSC Mei 2019) - Rezasyah, Teuku (Indonesia Center for Middle East Studies, 2019)
In May 2019, Indonesia served as President of the UN Security Council. During her presidency, Indonesia sought to achieve world peace by raising the theme